2016
DOI: 10.1556/004.2016.038
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of homologous recombination events in the evolution of bovine viral diarrhoea virus by in silico investigations

Abstract: Complete genome sequences of bovine viral diarrhoea virus types 1 and 2 (BVDV-1 and 2) deposited in the GenBank were submitted to bioinformatic analysis using a recombination-detecting software. The results indicate that recombination events are not rare in the case of BVDV, which frequently causes immunotolerance and, consequently, persistent infection in calves. The lack of specific immunity provides an ideal possibility for multiple infections by antigenically related but genetically different BVDV strains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Depending on the genomic region used for phylogenetic analysis, the two recombinant BVDV-1 strains, ILLNC and 3156, are classified as either BVDV-1a or BVDV-1b, while the genome of the BVDV-2 strain JZ05-1 resulted from a recombination event between BVDV-2a and BVDV-2b. A recent in silico study on the evolution of BVDV identified five recombinants among 61 available complete BVDV-1 genomic sequences and confirmed that recombination in BVDV is not rare and can occur among viruses belonging to the same subgenotype or between different subgenotypes [31]. In addition, RNA recombination can occur even between the two species BVDV-1 and BVDV-2 [32].…”
Section: Mechanisms Of Genetic Changes In Bvdv Genomesmentioning
confidence: 94%
See 1 more Smart Citation
“…Depending on the genomic region used for phylogenetic analysis, the two recombinant BVDV-1 strains, ILLNC and 3156, are classified as either BVDV-1a or BVDV-1b, while the genome of the BVDV-2 strain JZ05-1 resulted from a recombination event between BVDV-2a and BVDV-2b. A recent in silico study on the evolution of BVDV identified five recombinants among 61 available complete BVDV-1 genomic sequences and confirmed that recombination in BVDV is not rare and can occur among viruses belonging to the same subgenotype or between different subgenotypes [31]. In addition, RNA recombination can occur even between the two species BVDV-1 and BVDV-2 [32].…”
Section: Mechanisms Of Genetic Changes In Bvdv Genomesmentioning
confidence: 94%
“…Accordingly, RNA recombination, the emergence of cp BVDV, and pathogenesis of lethal mucosal disease are closely-linked processes [23]. Furthermore, homologous RNA recombination in pestivirus populations including BVDV-1 and BVDV-2 has been described [29,30,31]. Analysis of 125 complete pestivirus sequences provided evidence that the genomes of two BVDV-1, one BVDV-2, and four CSFV strains evolved from homologous recombination [30].…”
Section: Mechanisms Of Genetic Changes In Bvdv Genomesmentioning
confidence: 99%
“…This warrants further investigation. The continued evolution of the virus through high mutation rates and recombination with genetically related viruses 32 could lead to novel virus strains that may impair infection diagnosis, 28,29 control and possibly reduce vaccine efficacy 23 …”
Section: Discussionmentioning
confidence: 99%
“…This warrants further investigation. The continued evolution of the virus through high mutation rates and recombination with genetically related viruses 32 could lead to novel virus strains that may impair infection diagnosis, 28,29 control and possibly reduce vaccine efficacy. 23 The work presented here illustrates the value of sequencing data in BVD outbreak investigations, the need to incorporate it into conventional investigations of infection transmission networks and cluster analyses and its utility in surveilling emerging new strains and virus threats such as HoBi-like virus.…”
Section: Discussionmentioning
confidence: 99%